IMPLEMENTASI SIA PERSEDIAAN DAN PENJUALAN PADA PT MANTRI PANDITA PALEMBANG MENGGUNAKAN MICROSOFT ACCESS - Indah Purnama, Beauty; Armaini, Rosy; Setyadi, Bakti; Indriasari, Desi; Djuniar, Lis; Satriawan, Indra (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
PT Mantri Pandita is a PKM Partner which operates in the general trading sector in the form of selling office stationery, whose inventory and sales recording activities still use a manual system. The PKM Team took the initiative to help Partners by utilizing Microsoft Access, to design an Inventory and Sales Accounting Information System (AIS). Researchers collect technical data by means of observation and interviews. Primary data was obtained directly from the original source, namely the company PT Mantri Pandita, while secondary data was obtained through historical records and reports available in the company archives. This PKM target is to produce a computerized Inventory and Sales AIS, which is expected to help the Partner's warehouse and financial cashier departments in recording their business activities. Keywords: Accounting Information System, Sales&Inventory, Microsoft Access.